Life satisfaction and perceived overload as predictors of mental health in caregivers of psychiatric patients in the Peruvian Andes: A cross-sectional study - Calderon Apaza, Jorge Antonio (2026)
Introduction: Caregivers of psychiatric patients in the Peruvian Andes face unique challenges where most people do not receive the necessary health care. Objective: To analyze the association of life satisfaction and perceived competence with mental health, determining their incremental explanatory contribution after controlling for sociodemographic variables and perceived overload. Method: Cross-sectional study with 102 informal caregivers (85.3% women) recruited in four Community Mental Health Centers in Puno, Peru. Mental health (MHI-5), overload (Zarit), life satisfaction (SWLS), and sociodemographic variables were measured. A hierarchical linear regression analysis with bootstrapping (5000 samples, BCa) was performed to handle data non-normality, in addition to non-parametric comparisons (Kruskal-Wallis). Results: The final model explained 48.5% of the variance (R² adjusted = .48). Through bootstrapping, life satisfaction (β =0.41, p <.001) and perceived competence (β=−0.27, p=.004) showed robust significant associations with mental health. A displacement effect was observed where overload, significant in the first model, lost statistical significance (p =.103) upon introducing psychological resources. Likewise, a low level of instruction (primary and secondary) remained a significant risk factor compared to higher education. Conclusion: Self-perception of competence and life satisfaction act as protective factors that displace the direct impact of perceived overload.